2021
DOI: 10.3390/ijms222212208
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Protects against Noise-Induced Hearing Loss and Modulates Auditory Physiology in Female Mice

Abstract: Recent studies have identified sex-differences in auditory physiology and in the susceptibility to noise-induced hearing loss (NIHL). We hypothesize that 17β-estradiol (E2), a known modulator of auditory physiology, may underpin sex-differences in the response to noise trauma. Here, we gonadectomized B6CBAF1/J mice and used a combination of electrophysiological and histological techniques to study the effects of estrogen replacement on peripheral auditory physiology in the absence of noise exposure and on prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 85 publications
(119 reference statements)
1
19
0
Order By: Relevance
“…For control (no tamoxifen) GR male mice, credible intervals suggest near complete recovery of P1 amplitudes (BF 10 = 0.4, 95% CrI = −0.71 to 0.1). GR-related male noise vulnerability is consistent with reports of male susceptibility to sensory and neural hearing losses compared to noise susceptibility of females [ 53 , 54 , 55 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For control (no tamoxifen) GR male mice, credible intervals suggest near complete recovery of P1 amplitudes (BF 10 = 0.4, 95% CrI = −0.71 to 0.1). GR-related male noise vulnerability is consistent with reports of male susceptibility to sensory and neural hearing losses compared to noise susceptibility of females [ 53 , 54 , 55 ].…”
Section: Resultssupporting
confidence: 88%
“…Our observations of differential sensitivity to damage between male and female mice is consistent with a meta-analysis in which male rodents experienced greater hair cell loss and threshold shift compared to female rodents [ 102 ]. Studies have also found male vulnerability to mild noise exposure and P1 amplitude reduction [ 54 , 103 ], though see [ 53 ]. Recent investigation suggests that estrogen may directly modulate spiral ganglion neurons [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABR wave I is a measure of the response of multiple afferent fibers in the auditory nerve to sound, so larger ABR wave I amplitude suggests that females have greater synchrony of spiral ganglion neuron (SGN) afferent fibers or recruitment of more SGNs of a specific population at higher sound levels (Young et al, 2021). While sex hormones including estradiol and testosterone modulate auditory afferent synchrony in fish (Sisneros et al, 2004) and mice (Shuster et al, 2021), the underlying molecular mechanism of the sex difference in peripheral auditory processing in healthy inner ears of female and male mammals remains almost entirely unexplored. Understanding how healthy peripheral auditory systems differ between males and females is essential for tailoring specific hearing loss treatments and maintaining optimal auditory processing in both biological sexes.…”
Section: Introductionmentioning
confidence: 99%
“…NIHL is a complex disease and many factors have to be considered when establishing a new animal model. For example, both the melatonin of pigmented animals [ 75 ] and the estradiol of females [ 76 ] show a protective effect, so the selection of the animals is an important factor. Moreover, the circadian rhythm should be considered when planning the experimental setup [ 77 ].…”
Section: Discussionmentioning
confidence: 99%